ANALISIS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANG PADA CV X – BOGOR - Anessa Musfitria; Asti Handayani (Sekolah Tinggi Ilmu Ekonomi Gici, 2021)
Internal inventory control is a very important managerial function, as it affects the effectiveness and efficiency of the company's activities. Internal control over the supply of trade goods is necessary to reduce the risk of differences, losses, anticipate the possibility of fraud and ensure that procedures have been carried out properly so that improvements can then be made. With good control and regular in managing the inventory of trade goods, the company's leadership will be easier to obtain useful reports to improve the effectiveness of the company and help in making policy decisions and accountability in leading the company. This study aims to find out if internal control over the inventory of trade goods in CV X has been running effectively and efficiently. From the results of observation, interviews and analysis found that internal control in CV X has not been running effectively and efficiently.